Digital Applications as Assistive Technology for Students with Disabilities - Restianty, Ajani; Sumartias, Suwandi; Hadisiwi, Purwanti; Hafiar, Hanny (Universitas Pendidikan Indonesia (UPI), 2024)
This research aims to develop and design the application of assistive technology to transform the lives of individuals with disabilities, providing them with the skills and tools they need to overcome barriers that previously prevented them from fully participating in society. This research focuses on developing digital applications as a technological support for media lecturers to use in learning for students with disabilities. The research method used in this research is Design Based Research, which consists of three main stages, namely needs assessment, design process, technology used, and making interactive prototypes. Current developments in assistive technology and disability research indicate a growing interest in using assistive technology to promote inclusive practices in the pursuit of knowledge. There is a focus on creating diverse and culturally adaptive learning environments that suit diverse needs and experiences and increasing awareness of society's challenges and prejudices when using assistive technology. Adopting digital apps as assistive technology is not only a huge step toward making educational settings more inclusive and accessible for students with disabilities but also provides a variety of capabilities to meet the different requirements of students, such as configurable displays, interactive and multisensory learning possibilities, and interaction with other assistive technology.